Herbal monomer–based therapeutic insights from traditional Chinese medicine in myocardial infarction - Bian, Nan; Xia, Libo; Xiong, Xianqiu; Chen, Yingyu; Chen, Ying (Frontiers in Molecular Biosciences, 2026)
Myocardial infarction (MI) is a leading cause of morbidity and mortality globally, often resulting in heart failure due to adverse cardiac remodeling triggered by inflammation and fibrosis. Traditional Chinese Medicine (TCM), particularly compounds like Quercetin from Licorice and Peony, has shown promise in modulating inflammation and oxidative stress in cardiovascular diseases. This study integrates bioinformatics and experimental validation to explore the therapeutic potential of Quercetin in MI. Using Mendelian Randomization (MR) and colocalization analysis, we identified key MI-related genes, such as VEGFA, PTK2, and GGT1, whose expression is influenced by Quercetin. Bioinformatics tools predicted these genes as targets of Quercetin, with molecular docking revealing stable interactions between the compound and these genes. Single-cell RNA-sequencing of MI samples confirmed the expression of these genes in cardiac muscle cells (CMs) and macrophages, highlighting their role in tissue repair and inflammation. In experimental models, Quercetin treatment significantly altered the expression of these genes, enhancing myocardial cell recovery and reducing infarct size. This study provides molecular insights into how Quercetin and other TCM compounds could modulate critical pathways involved in MI recovery, supporting their potential as adjunct therapies. The findings bridge traditional medicine with modern bioinformatics, opening new avenues for therapeutic strategies to improve cardiac function and patient outcomes in MI.